2017
DOI: 10.1186/s13065-016-0230-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic, dielectric, molecular docking and DFT studies of (3E)-3-(4-methylbenzylidene)-3,4-dihydro-2H-chromen-2-one: an anticancer agent

Abstract: BackgroundCoumarin (2H-chromen-2-one) and its derivatives have a wide range of biological and pharmaceutical activities. They possess antitumor, anti-HIV, anticoagulant, antimicrobial, antioxidant, and anti-inflammatory activities. Synthesis and isolation of coumarins from different species have attracted the attention of medicinal chemists. Herein, we report the synthesis, molecular structure, dielectric, anticancer activity and docking studies with the potential target protein tankyrase.ResultsMolecular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…Thus, coumarin inhibits the growth and proliferation of tumor cells at low concentrations [59,60]. It was reported that some coumarin derivatives have cytotoxic activity and docking studies have revealed that the potential target of coumarin is the tankyrase enzyme [61]. According to the molecular docking results in our study, the binding potential of coumarin to tankyrase shows us that coumarin may act as a potential tankyrase inhibitor.…”
Section: Cytotoxic Activitysupporting
confidence: 58%
“…Thus, coumarin inhibits the growth and proliferation of tumor cells at low concentrations [59,60]. It was reported that some coumarin derivatives have cytotoxic activity and docking studies have revealed that the potential target of coumarin is the tankyrase enzyme [61]. According to the molecular docking results in our study, the binding potential of coumarin to tankyrase shows us that coumarin may act as a potential tankyrase inhibitor.…”
Section: Cytotoxic Activitysupporting
confidence: 58%
“…Furthermore, 4‐hydroxycoumarin was used to reduce the reverse transcriptase activity of ACH‐2‐lymphocyte affected by the HIV [21] and the acylation of hydroxy groups at C‐7&C‐8 positions of 7,8‐dihydroxycoumarin and C‐7 position of the 7‐hydroxycoumarin skeleton were elucidated the changing of G‐protein‐coupled receptor activators into inhibitors [22,23] . Moreover, 3 E ‐3‐(4‐methylbenzylidene)‐3,4‐dihydro‐2H‐chromen‐2‐one and Warfarin derivative were found to an excellent anticancer agent to MCF‐7 and HT‐29 cells with diverse concentrations exhibited considerable cytotoxicity for breast cancer peoples [24] and 7‐(carboxymethoxy)‐4‐methyl coumarin was prescribed to patients who suffered with upper or lower limb i. e., lymphedema disease [25] . Due to heterocyclic conformational discrepancy in the coumarin derivatives of 1,2,3‐Triazole, these compounds project fascinating aspects to have specific binding with tumor cells and to control the growth of cancer cells in mitochondria and human serum albumin [26,28] …”
Section: Introductionmentioning
confidence: 99%